Enhancing minority student retention and academic performance what we can learn from program evaluations - Fleming, Jacqueline, 1947- (Jossey-Bass, 2012)
"In this important resource, Dr. Fleming (a noted expert in the field of minority retention) draws on educational evaluations she has developed in the course of her distinguished career. This book analyzes the common factors and the role institutional characteristics play in minority student retention to show what really works in increasing academic performance among minority students and includes models of evaluations that describe successful programs that use statistical methods to verify outcomes"--